Processamento do pronome átono "lhe" em português brasileiro : comparando dados da Paraíba e do Rio de Janeiro - Gomes, Milena Magalhães (2025)
This study aims to analyze the influence of the diatopic factor on the processing of the pronoun lhe in two different speech communities of Brazilian Portuguese (BP): Paraíba and Rio de Janeiro. The research is grounded in the framework of Experimental Psycholinguistics while also drawing on the perspective of Variationist Sociolinguistics, in order to identify potential regional differences in the use of lhe between the two regions under study. It examines variations at both the grammatical and discourse levels with the goal of investigating the cognitive dimension of linguistic variation. This analysis is supported by evidence of an ongoing reinterpretation of the clitic lhe, observed in several BP speech communities, with particular emphasis on the Northeast region of Brazil, where its use extends beyond the patterns prescribed by traditional grammar compendia (Almeida, 2009; Oliveira, 2020a). Methodologically, this work consists of a quantitative and experimental study through the implementation of a Self-Paced Reading experiment. The goal is to assess the processing cost of the pronoun lhe when used to refer to the second person singular (2SG) and third person singular (3SG), in both dative and accusative contexts, by speakers from Rio de Janeiro in comparison to speakers from Paraíba. The following hypotheses were proposed: a) the pronominal form lhe exhibits dialectal variation between speakers from Rio de Janeiro and Paraíba; b) the referential function of the pronoun lhe is processed similarly in both speech communities; c) the pronoun lhe is processed differently at the syntactic level between speakers from the two regions; d) sociolinguistic factors may influence the processing of the linguistic structures under analysis. The results showed that sociolinguistic factors can influence the processing of linguistic structures. The interaction between the factors discourses feature, pronoun function, and participant's state of origin resulted in significant differences in processing patterns among participants. Furthermore, when analyzing the participant's state of origin factor in isolation, it was possible to verify that clitics have a lower processing cost among speakers from Paraíba compared to speakers from Rio de Janeiro, confirming the hypothesis of dialectal variation between both speech communities.